Application of Electrolyzed Hydrogen Water for Management of Chronic Kidney Disease and Dialysis Treatment-Perspective View - Masaaki Nakayama; Shigeru Kabayama; Mariko Miyazaki (MDPI AG, 2024)
Chronic kidney disease (CKD), which is globally on the rise, has become an urgent challenge from the perspective of public health, given its risk factors such as end-stage renal failure, cardiovascular diseases, and infections. The pathophysiology of CKD, including dialysis patients, is deeply associated with enhanced oxidative stress in both the kidneys and the entire body. Therefore, the introduction of a safe and widely applicable antioxidant therapy is expected as a measure against CKD. Electrolyzed hydrogen water (EHW) generated through the electrolysis of water has been confirmed to possess chemical antioxidant capabilities. In Japan, devices producing this water have become popular for household drinking water. In CKD model experiments conducted to date, drinking EHW has been shown to suppress the progression of kidney damage related to hypertension. Furthermore, clinical studies have reported that systemic oxidative stress in patients undergoing dialysis treatment using EHW is suppressed, leading to a reduction in the incidence of cardiovascular complications. In the future, considering EHW as one of the comprehensive measures against CKD holds significant importance. The medical utility of EHW is believed to be substantial, and further investigation is warranted.